Unveiling the socio-cultural practices of medicinal plants used by the ethnic community of Soliga tribes in Tamil Nadu, India - Chinnasamy Menaka; Annadurai Logamadevi; Arumugam Vignesh (Phytomedicine Plus)
Background and purpose: Plants have been integral to human health and cultural traditions for millennia, representing a vital relationship between tribal communities and their natural environment. The Soliga tribes have developed a profound relationship with the flora of their natural environment, utilizing various plant species in their socio-cultural practices. These practices are closely connected with their traditional knowledge, spirituality, and everyday life. This study aimed to document the socio-cultural practices associated with plant species and to identify the most culturally significant species used by the Soliga tribes in Anthiyur Taluk, Erode District, Tamil Nadu, India. Methods: Ethnobotanical insights were collected through semi-structured interviews, group discussions, questionnaires, and field observations with knowledge holders. The collected data were analyzed using basic variables and ethnobotanical indices, whereas relationships and patterns within the dataset were explored through Pearson correlation and Principal component analysis (PCA). Results: A total of 47 plant species from 25 families and 42 genera were identified as central to socio-cultural practices. Among these, Fabaceae, Apocynaceae, and Lamiaceae emerged as the predominant families. Achyranthes aspera L. was found to have the highest cultural importance index (CI) value of 0.98, followed by Cassia fistula L. and Lantana camara L. with CI values of 0.96 each. Ethnobotanical indices such as cultural importance index (CI), relative frequency of citation (RFC), relative importance index (RI) and cultural value index (CV) were applied, revealing significant positive correlations between basic variables and indices, such as CI and use reports (UR) (r = 0.82). Principal Component Analysis (PCA) further demonstrated that variables such as CI and RFC accounted for 60.24 % of the variance in the data. Conclusions: The findings underscore the deep interconnection between Soliga tribes’ traditional knowledge and plant biodiversity, highlighting the urgency of preserving these cultural and ecological resources for future generations.